Proceedings of the DESIGN 2018 15th International Design Conference 2018
DOI: 10.21278/idc.2018.0211
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Function Integrity Diagnosis and Documentation: Fidd

Abstract: This paper introduces a method to perform systematic diagnosis of function integrity. The proposed method advances the Integrated Function Modelling framework to extend its application to risk identification and documentation tasks. By analyzing the system model of interdisciplinary designs, this method guides the designer to explore function vulnerability by systematic decoupling of inherent design entities. Thereby it provides unique opportunities for failure mode identification in complex, interdisciplinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A concept assessment method for product adaptation should balance pragmatism with detail to achieve high effectiveness with efficiency. To create a sufficient compromise, the FIDD method applies a system modelling approach for concept analysis (Wichmann et al, 2018). The (I)ntegrated (F)unction (M)odelling (IFM) framework was selected because it provides opportunity to integrate design concepts in an (I)ntegrated (F)unction (IF) model (Eisenbart et al, 2017).…”
Section: Concept Risk Identification and Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A concept assessment method for product adaptation should balance pragmatism with detail to achieve high effectiveness with efficiency. To create a sufficient compromise, the FIDD method applies a system modelling approach for concept analysis (Wichmann et al, 2018). The (I)ntegrated (F)unction (M)odelling (IFM) framework was selected because it provides opportunity to integrate design concepts in an (I)ntegrated (F)unction (IF) model (Eisenbart et al, 2017).…”
Section: Concept Risk Identification and Assessmentmentioning
confidence: 99%
“…Once an IF Model of the to-be adapted product or subsystem is created (see Gericke and Eisenbart, 2017) the FIDD method defines an approach in how to diagnose (identify) risks and their failure modes (see Figure 2). The seven step approach (see Wichmann et al, 2018) offers guidelines to analyse an IF model following a logical sequence that scrutinises the modelled entities. The identified failure modes can be documented in an extended template of a generic FMEA supporting the designer to track any failure mode to an overarching function and use-case.…”
Section: Concept Risk Identification and Assessmentmentioning
confidence: 99%
“…This implies a possibility of research that would realize the pathway "closing" the loop originating from [34] in a figure eight as depicted by Figure 8. In fact, outside the genealogy, a research work is found [57] citing Ref. [42], which proposed a method to explore function vulnerability and identify failure modes in complex systems and then applied it to a case from industry.…”
Section: Implications For Research On Scpmentioning
confidence: 99%
“…[42], which proposed a method to explore function vulnerability and identify failure modes in complex systems and then applied it to a case from industry. This means that the authors of [57] developed the method first in a theoretical field and thereby the loop is nearly closed. Several aspects of interest can be analysed looking into further details of this genealogy combined with the author's reflection of his own activity in this research.…”
Section: Implications For Research On Scpmentioning
confidence: 99%
See 1 more Smart Citation